A framework to represent, capture, and trace ontology development processes. (November 2016) - Vegetti, Marcela; Roldán, Luciana; Gonnet, Silvio; Leone, Horacio; Henning, Gabriela
Abstract: This article presents OntoTracED, a comprehensive framework to represent, capture and trace ontology development processes. It has three components: (i) a conceptual model that defines the framework foundations, (ii) an ontological engineering domain model (OEDM), which specifies and describes design objects, as well as those operations that are particular to a specific ontology development methodology, and (iii) a computational support environment, named TracED(aaS). This contribution first offers an overview of the ontology development process characteristics and then describes the main features of each OntoTracED component. The framework capabilities are illustrated by means of a case study addressing the use of TracED(aaS) throughout the development of an ontology of industrial interest. It is shown that this proposal makes a strong contribution in the ontological engineering field since the whole ontology development process, its history, rationale, and all the intermediate products can be captured in an integrated fashion.